The tectonic control over dykes and dyke swarms of the Ukrainian Shield - Shatalov, N.N. (Reports of the National Academy of Sciences of Ukraine, 2014)
The lateral features of the tectonics for the Ukrainian Shield are revealed. The structure-tectonic position of dykes and dyke swarms within the Ukrainian Shield are determined by the structure-tectonic data.